Testing Media Richness Theory in the New Media: The Effects of Cues, Feedback, and Task Equivocality - Dennis, Alan R; Kinney, Susan T (Information systems research, 1998)
Media richness theory argues that performance improves when team members use "richer" media for equivocal tasks. This experiment studied the effects of media richness on decision making in two-person teams using "new media" (i.e., computer-mediated and video communication). Media richness was varied based on multiplicity of cues and immediacy of feedback. Subjects perceived differences in richness due to both cues and feedback, but matching richness to task equivocality did not improve decision quality, decision time, consensus change, or communication satisfaction. Use of media providing fewer cues (i.e., computer mediated communication) led to slower decisions and more so for the less equivocal task. In short, the results found no support for the central proposition of media richness theory; matching media richness to task equivocality did not improve performance.